2017
DOI: 10.1038/s41559-017-0377-2
|View full text |Cite
|
Sign up to set email alerts
|

Complexity and conservation of regulatory landscapes underlie evolutionary resilience of mammalian gene expression

Abstract: To gain insight into how mammalian gene expression is controlled by rapidly evolving regulatory elements, we jointly analysed promoter and enhancer activity with downstream transcription levels in liver samples from fifteen species. Genes associated with complex regulatory landscapes generally exhibit high expression levels that remain evolutionarily stable. While the number of regulatory elements is the key driver of transcriptional output and resilience, regulatory conservation matters: elements active acros… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

18
134
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 133 publications
(161 citation statements)
references
References 82 publications
18
134
0
Order By: Relevance
“…6b) and the number of loop interactions with distal sites. These observations are also compatible with those made very recently in liver tissue 47 . In addition, we find a strong correlation in the opposite direction at the distal end of loops, where promoters that form more loop interactions have enhancers that are less, rather than more, conserved at the level of both transcription (Fig.…”
Section: Discussionsupporting
confidence: 93%
“…6b) and the number of loop interactions with distal sites. These observations are also compatible with those made very recently in liver tissue 47 . In addition, we find a strong correlation in the opposite direction at the distal end of loops, where promoters that form more loop interactions have enhancers that are less, rather than more, conserved at the level of both transcription (Fig.…”
Section: Discussionsupporting
confidence: 93%
“…The relative importance of conserved and novel enhancers remains an open question that is of significant interest to the field. It has been suggested that recently evolved enhancers have a somewhat smaller effect on gene expression than shared/conserved elements and have a slight association with genes showing evolutionarily stable expression levels (Berthelot et al 2018). It also remains unclear the degree to which selection pressures have driven convergent, functional sequence changes such as in transcription factor binding sites in TWARs.…”
Section: Discussionmentioning
confidence: 99%
“…Over the recent years, since more systematic perturbative experiments of candidate non-coding sequences have become possible, we have learned that mammalian regulatory landscapes are extremely complex and often contain redundant enhancers and that the impact of individual putative enhancer deletion/silencing on expression of target genes is dependent on inherent enhancer strength, number and strength of other active enhancers acting on the same gene in a given cell type, and spatial constraints reflected in the frequency of contact with the target promoter(s) [59][60][61][62][63]. Furthermore, while relationships among enhancers within a regulatory landscape are often additive [64], examples of other relationships, including synergistic, competitive and hierarchical, have been described in the literature (reviewed in [42]). We should expect that TE-derived enhancers will participate in these complex relationships and thus their activity (or lack thereof ) should be interpreted in a broader context of a given regulatory landscape.…”
Section: Transcription Of Merv-l/herv-h Elements Establishes Cell-typmentioning
confidence: 99%